Productivity, Forage Quality and Economics of Guinea Grass and Caribbean Stylo Intercropping Systems
A field experiment was conducted on sandy loam soil for ’four consecutive years (2003-04 to 2006-07) at Central Research Farm of Indian Grassland and Fodder Research Institute, Jhansi, to study the effect of row ratios (grass sole, legume sole, 1:1, 2:2, 3:3 and 4:4) and fertility levels on growth, productivity, quality and monetary return of Guinea grass - S. hamata intercropping system under rainfed conditions. Intercropping of Guinea grass with S. hamata in 2:2 row ratio produced significantly higher dry forage (5.01 t ha-1) and crude protein yields (438.8 kg ha-1 ) as compared to sole crop or alternate rows of both grass and legumes, and it was at par with 3:3 and 4:4 row ratios. The dry matter yields of the recommended dose of fertilizer was reduced by 28.32% over 75% of RDF + 5 t ha-1 FYM. Intercropping of Guinea grass with S. hamata in all the row ratios resulted in land equivalent ratio greater than 1, indicating intercr9pplng